National Culture in the Language of Politics - Zięba, Anna (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2011)
The objective of this paper is to prove that linguistic manifestations of cultural differences can be found in texts produced in culturally distinct environments. Hofstede’s 5D model concerning cultural differences will be presented and applied to an analysis of two texts: speeches delivered by the Polish Prime Minister, Donald Tusk, and the British Prime Minister, Gordon Brown. It will be shown that specific characteristics of both texts correspond to the cultural dimensions introduced in the 5D model, especially the dimension of power distance, the dimension of individualism vs. collectivism and the dimension of uncertainty avoidance. The importance of the implementation of the results of such an analysis will be underlined, especially in the context of migration. It will be proven that the linguistic application of Hofstede’s model seems to be an indispensible tool in the research into the pragmatics of intercultural communication. It may also be helpful in preparing acculturation courses for future expatriates who are bound to experience a cultural shock. The paper is based on literature on intercultural communication and text analysis and the transcripts of both speeches.
Keywords: Politics; Culture